Limited Health Literacy and Patient Confusion About Rheumatoid Arthritis Patient Global Assessments and Model Disease States. Issue 5 (10th April 2019) - Hirsh, Joel; Wood, Patrick; Keniston, Angela; Peng, Mandy; Ramaswami, Sai; Caplan, Liron; Davis, Lisa
Abstract : Objective: Patient global assessment visual analog scales (PGA‐VAS) are widely used in rheumatoid arthritis (RA) practice and research, and low PGA‐VAS scores are required for remission. Vulnerable patients with RA may have difficulty completing the PGA‐VAS. There is limited information about both patients' perceptions of PGA‐VAS and how patients score VAS model disease states. The objective of this study was to understand the perspectives of vulnerable patients regarding PGA‐VAS and model disease states. Methods: We enrolled patients with RA at Denver Health (n = 300). Subjects completed the PGA‐VAS in the Disease Activity Score in 28 joints and the Multidimensional Health Assessment Questionnaire and completed a questionnaire regarding these PGA‐VAS. Subjects also scored remission, mild, moderate, and severe model disease states by VAS. We performed analyses by linear and logistic regression and by using summary statistics. Outcomes included whether subjects found the PGA‐VAS confusing, whether subjects' responses to the model disease states followed a natural progression (remission <mild <moderate <severe), and whether responses to the remission model would meet Boolean and Simplified Disease Activity Index–based remission criteria. Results: Approximately 40% of subjects found the PGA‐VAS confusing; lower health literacy and depressive symptoms were associated with finding them confusing. Less than 25% of subjects ranked the model disease states with natural progression and ranked the remission model at the threshold for remission; higher health literacy and income were associated with accomplishing these objectives. Conclusion: Vulnerable patients perceive difficulty with PGA‐VAS and do not reliably rate a model disease state VAS. These patients are potentially at risk for disease activity misclassification because of literacy and other barriers in completing VAS.